Literasi Media Digital dalam Membentuk Sikap Kritis Bermedia Sosial pada Siswa MTS Kabila di Kecamatan Tilongkabila Kabupaten Bone Bolango - Mohamad Yudiansyah Pratama; Hariana Hariana; Trifandi Lasalewo (Politeknik Kebangsaan, 2026)
This article describes the implementation of a media literacy socialization program aimed at developing critical digital thinking skills among students at MTs Muhammadiyah Kabila by students participating in the Gorontalo State University Community Service Program in Permata Village in 2025. This program was motivated by the high exposure of teenagers to digital information, which is often not balanced with the skills to sort and understand information wisely. The activities were carried out using a participatory approach through counseling, interactive discussions, and digital content analysis practices, which were designed based on the identification of student needs and concluded with an evaluation of the program's effectiveness. The results of the activities showed an increase in students' understanding of recognizing hoaxes, applying social media ethics, and developing a critical attitude towards the rapid and diverse flow of digital information. Through this activity, students not only gained theoretical insights but also practical experience in dealing with digital literacy issues in their daily lives. Thus, this article concludes that media literacy socialization makes a positive contribution in equipping students with critical digital skills relevant to facing the challenges of the digital age and can be used as a reference for implementing similar programs in other educational environments.